2-(4-Hydroxyphenyl)acetic acid–4,4′-bipyridine (1/1) - Liu, Jian-Feng (International Union of Crystallography, 2010)
In the acid molecule of the title complex, C(10)H(8)N(2)·C(8)H(8)O(3), the acetyl C—C—C—O torsion angle is −32.1 (3)°, and in the molecule of the base, the dihedral angle between the two pyridine rings is 23.41 (10)°. In the crystal structure, intermolecular O—H⋯N hydrogen bonds link the acid and the base molecules into a one-dimensional triple-helix framework extended along the b axis.